2015
DOI: 10.1186/s13195-015-0159-5
|View full text |Cite
|
Sign up to set email alerts
|

Diagnostic value of cerebrospinal fluid Aβ ratios in preclinical Alzheimer’s disease

Abstract: IntroductionIn this study of preclinical Alzheimer’s disease (AD) we assessed the added diagnostic value of using cerebrospinal fluid (CSF) Aβ ratios rather than Aβ42 in isolation for detecting individuals who are positive on amyloid positron emission tomography (PET).MethodsThirty-eight community-recruited cognitively intact older adults (mean age 73, range 65–80 years) underwent 18F-flutemetamol PET and CSF measurement of Aβ1-42, Aβ1-40, Aβ1-38, and total tau (ttau). 18F-flutemetamol retention was quantified… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
53
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 45 publications
(57 citation statements)
references
References 43 publications
(54 reference statements)
4
53
0
Order By: Relevance
“…This discrepancy is likely due to the differences in the cohorts (higher numbers of cognitively normal individuals expected to be in the preclinical period in the current cohort) and/or different methodological issues. Another study reported no significant differences in concordances between Aβ 42/40 and Aβ 42 with amyloid PET, although the AUC for Aβ 42/40 was slightly larger than that for Aβ 42 alone [37]. This lack of significance might be attributed to the lower statistical power (a much smaller cohort, n  = 38) and/or the use of different ELISAs and PET tracer ( 18 F-flutemetamol) in that study.…”
Section: Discussionmentioning
confidence: 72%
“…This discrepancy is likely due to the differences in the cohorts (higher numbers of cognitively normal individuals expected to be in the preclinical period in the current cohort) and/or different methodological issues. Another study reported no significant differences in concordances between Aβ 42/40 and Aβ 42 with amyloid PET, although the AUC for Aβ 42/40 was slightly larger than that for Aβ 42 alone [37]. This lack of significance might be attributed to the lower statistical power (a much smaller cohort, n  = 38) and/or the use of different ELISAs and PET tracer ( 18 F-flutemetamol) in that study.…”
Section: Discussionmentioning
confidence: 72%
“…The cut‐off for CSF Aβ 1–42 to predict amyloid‐PET positivity was 745 pg/mL and was previously defined on the same cohort (Adamczuk et al . ). The CSF Aβ 1–42 cut‐off of 745 pg/mL was derived by calculating the area under the curve in a receiver operating characteristics approach for which the Youden criterium was applied to select the optimal cut‐off, i.e.…”
Section: Methodsmentioning
confidence: 97%
“…the best compromise between high sensitivity and high specificity (area under the curve: 0.908, 100% sensitivity and 74.19% specificity) (Adamczuk et al . ). The standard of truth for the receiver operating characteristics analysis in that study was amyloid‐positivity based on an autopsy validated amyloid‐PET SUVRcomp cut‐off of 1.57 (Adamczuk et al .…”
Section: Methodsmentioning
confidence: 97%
See 2 more Smart Citations